Memory work in the classroom to understand the policies of state terrorism and dehumanization of Chile (Clepsidra - Interdisciplinary Journal of Memory Studies, 2021)
This article analyses the case of three memory didactic strategies for the comprehension of state terrorism and dehumanization in the recent history and the pedagogical practices in which they are sustained in an educational center between 2015 and 2018. The implemented strategies for the testimonial memory, the social and emblematic memory, and the visit to memory places strengthen the historical view of the human rights violations in young people. At the same time, comprehension and historic empathy of a catastrophic past and the complexity implied in the present are promoted among them. The development of these pedagogical practices contributes to encourage autonomous teams which have kept away from reproductive curriculum positions and also promotes the students critical thinking in a public area.
Keywords: recent history, memory, human rights, teaching